Analisis Kondisi Keuangan Kabupaten Kota di Provinsi Sumatera Utara - Laelisneni, Laelisneni; Lily Karlina Nasution; Mayang Murni; Agustina Nurul Fajriah; Nurlela Nurlela (Worksheet : Jurnal Akuntansi, 2026)
Regional finance is a fundamental aspect in supporting economic development and improving the welfare of the community in a region. The management of regional finances reflects the ability of local governments to plan, implement, and account for all financial activities efficiently and transparently. The aim of this study is to analyze the financial condition of regencies and cities in the Aceh Province. This study uses a qualitative descriptive method with secondary data sourced from reports of the Regional Finance and Asset Agency (BPKA) of North Sumatra Province and the Central Statistics Agency (BPS). The indicators used to assess financial conditions are service solvency, financial flexibility. The research found that the financial condition of regencies and cities in North Sumatra Province shows that only one regency/city, Asahan, has a poor financial condition. Meanwhile, 14 regencies/cities have a moderate financial condition. The good category is held by 4 regencies/cities (Medan, West Pakpak, Pematang Siantar, and Sibolga). This study can serve as a policy recommendation for improving financial management in regencies/cities in North Sumatra Province.Keywords : Financial Condition; Service Solvency; Financial Flexibility; Financial Independence; North Sumatra Province